Peningkatan Pemahaman Mengenai Kasih Allah Dan Iman Kristiani Kepada Persekutuan Pemuda-Pemudi GMI Manna Balige - Kasih Situmorang; Natalia Rotua Sianipar; Novia Sari Saragih; Renisha Wikawanty Lumban Raja; Lestari Br. Silaban; Yubilate Chriswell Zebua (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
A deep understanding of God's love and Christian faith is an important aspect in the spiritual life of every individual, especially the younger generation in the church. This article discusses efforts to increase understanding of God's love and Christian faith among the GMI Manna Balige youth association. The research method used is a quantitative approach through holding seminars which include material delivery, question and answer sessions, and interactive discussions. Evaluation is carried out through interview sessions to measure participant understanding. The results showed positive changes in participants' understanding and awareness of these concepts. It is hoped that this article can contribute to strengthening faith and love in the church community, as well as being a guide for developing similar programs in other churches.